Modelling of an equivalent circuit for Cu2ZnSnS4- and Cu2ZnSnSe4-based thin film solar cells. Issue 41 (11th May 2017) - Shibayama, Naoyuki; Zhang, Yiwen; Satake, Tetsuo; Sugiyama, Mutsumi
Abstract : The internal resistance and quality of the interface in CZTS solar cells were investigated using electrochemical impedance spectroscopy. Abstract : The internal resistance and quality of the interface in Cu2 ZnSn(S, Se)4 (CZT(S, Se)) solar cells were investigated using electrochemical impedance spectroscopy (EIS). We developed an equivalent circuit of the CZT(S, Se) solar cell involving the contact and material resistances R bulk, two parallel resistances, and a 'capacitance-like element' called a constant phase element (CPE) around the CZT(S, Se)/CdS heterojunction and Mo–Mo(S, Se)2 /CZT(S, Se) back-contact interfaces. Using the EIS method, the states of Mo(S, Se) and the CZT(S, Se) layer could be digitised non-destructively. This result can provide guidelines for improving the performance of CZT(S, Se) solar cells or any semiconductor device.